Impact of Supreme Court Case Law on some Issues Concerning Damage Compensation from the Mandatory Liability Insurance of Motorists - Samson, Maciej (Studia Oeconomica Posnaniensia, 2015)
This paper assesses the impact of Supreme Court case law for motor liability compensation in terms of a replacement vehicle rental and use and the depreciation of the parts used for repair. The paper compares the position of Insurance Ombudsman presented in the report The Case Law of the Supreme Court and the Practice of Handling Motor Insurance Claims with selected publications containing other proposals, and assesses the legal position of the decisions of the Supreme Court regarding the principles and practice of settling claims.